2008
DOI: 10.1152/ajpregu.00453.2007
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of brain mast cells by compound 48/80, a histamine liberator, evokes renin and vasopressin release in dogs

Abstract: Because degranulation of brain mast cells activates adrenocortical secretion ( 41 , 42 ), we examined whether activation of such cells increases renin and vasopressin (antidiuretic hormone: ADH) secretion. For this, we administered compound 48/80 (C48/80), which liberates histamine from mast cells, to pentobarbital-anesthetized dogs. An infusion of 37.5 μg/kg C48/80 into the cerebral third ventricle evoked increases in plasma renin activity (PRA), and in plasma epinephrine (Epi) and ADH concentrations. Ketotif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…This is a condensation product of p-methoxyphenethyl-methylamine and formaldehyde originally described as histamine liberator (2,43). Later, it was demonstrated that histamine can be released along with other compounds like 5-HT and epinephrine (9,36). As shown in Fig.…”
Section: Tph Aadc Mao-mentioning
confidence: 94%
“…This is a condensation product of p-methoxyphenethyl-methylamine and formaldehyde originally described as histamine liberator (2,43). Later, it was demonstrated that histamine can be released along with other compounds like 5-HT and epinephrine (9,36). As shown in Fig.…”
Section: Tph Aadc Mao-mentioning
confidence: 94%
“…This chronically administered dose is comparable to that used to prevent mast cell degranulation in dogs. 15,16 Treatment was started 24 hours after MR induction. Only 5 of 9 untreated MR dogs (male = 3; female = 2) and 4 of 6 MR dogs treated with MCS (male = 3; female = 1) survived to four months.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 Ketotifen is a histamine H 1 receptor and calcium entry antagonist that inhibits the release of leukotrienes and improves β-adrenoreceptor sensitivity. 9 Here we show that MCS does not attenuate eccentric LV remodeling nor does it preserve interstitial collagen after four months of MR in the dog.…”
Section: Introductionmentioning
confidence: 99%
“…This can also be proved by the fact that H1 receptor blockers decrease cortisol secretions. In animal studies, histamine release from brain MC may increase renin and epinephrine secretion (through splanchnic nerves) and antidiuretic hormone secretion (through central nervous system) [20,21]. They also seem to influence pituitary-thyroid action.…”
Section: Mast Cells In Brain's Physiologymentioning
confidence: 99%